1987
DOI: 10.1021/bi00387a005
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium ions and the heavy chain of factor XIa in the activation of human coagulation factor IX

Abstract: Since optimal rates of factor IX activation by factor XIa require the presence of calcium ions and the heavy chain of the enzyme as well as the active-site-containing light chain, we have studied the effects of calcium ions and the heavy chain on the reaction kinetics. Whereas the amidolytic activities of factor XIa and of its active-site-containing light chain were almost indistinguishable, the two enzymes behaved quite differently when factor IX was the substrate. Factor XIa was 100-fold more potent in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
51
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 25 publications
10
51
0
Order By: Relevance
“…Our conclusion that FXI zymogen activation is accompanied by major changes in domain structure is further supported by biochemical data indicating that the binding properties of FXIa differ from those of the zymogen with respect to its substrate, FIX, and the platelet surface (29)(30)(31). These observations are consistent with domain rearrangements exposing new binding sites upon conversion of FXI into FXIa.…”
Section: Domain Structure Of Fxi and Fxia Observed By Saxs And Emsupporting
confidence: 84%
“…Our conclusion that FXI zymogen activation is accompanied by major changes in domain structure is further supported by biochemical data indicating that the binding properties of FXIa differ from those of the zymogen with respect to its substrate, FIX, and the platelet surface (29)(30)(31). These observations are consistent with domain rearrangements exposing new binding sites upon conversion of FXI into FXIa.…”
Section: Domain Structure Of Fxi and Fxia Observed By Saxs And Emsupporting
confidence: 84%
“…The wells were then incubated with 100 l/well of 1 g/ml of 5F4, a FXI light chain-specific monoclonal antibody, for 1 h at 37°C. Since the 5F4 monoclonal antibody binds with high affinity to FXIa (K d ϳ0.78 ϫ 10 Ϫ10 M) (37) and a saturating concentration of antibody (6.3 ϫ 10 Ϫ9 M) was used, this assay provides an excellent determination of bound FXIa. After washing, 100 l per well of a 1:1000 dilution of alkaline phosphatase-conjugated goat anti-mouse antibody was added for a 1-h incubation at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…There is compelling evidence that one or more exosites (substrate binding sites distinct from the protease active site) on fXIa are required for normal fIX activation (17)(18)(19)(20)(21)(22)(23), but there is a lack of agreement on their locations. It is clear that Ca 2ϩ -dependent fIX activation requires the fXIa heavy chain (19,20).…”
mentioning
confidence: 99%
“…It is clear that Ca 2ϩ -dependent fIX activation requires the fXIa heavy chain (19,20). One report indicated that the A2 domain contains a fIX binding site (21), whereas others point to A3 (22,23).…”
mentioning
confidence: 99%